(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
• In the digital age, the integration of digital technologies has significantly transformed the teaching and learning of English in higher education. This article examines the effective organization of English language lessons through the use of digital tools such as online learning platforms, interactive applications, multimedia resources, mobile applications, and artificial intelligence–based technologies. The study highlights how these tools enhance learner engagement, interactivity, personalization, and flexibility while shifting the teacher’s role from information provider to facilitator and mentor. The findings suggest that digital technologies contribute to improved learning outcomes, increased student motivation, and the development of autonomous and communicative language skills.